Pengaruh ZPT terhadap Kualitas Buah Manggis - Juanasri Juanasri; Roedhy Poerwanto (Agrovigor, 2008)
The objectives of this experiment was to examine the influence of polyamine, gibberellin and harvesting times to inhibit ripening process and to maintain the postharvest quality on mangosteen. The method applied was a randomized block design with two factors and three replications. First factor was harvesting time consisting of 14, 15 and 15 weeks after anthesis. Second factor is chemical concentration consisting of control (aquadest), GA3 (150, 200, 250 mg/l), polyamine (0,3; 1 and 3 mM). The result showed that spermidine application at 1 mM was more effective to maintain the postharvest quality of mangosteen, the fruit remained soft and the climacteric peak was longer than that of control. Gibberellin application showed unsightly result compared to control. Mangosteen fruits with harvesting time of 15 and 16 weeks after anthesis had better performance than those of harvesting at 14 weeks after anthesis, the fruit has remained soft and the weight loss was less.